Body fat differences among US youth aged 8–19 by race and Hispanic origin, 2011–2018. Issue 7 (8th February 2022) - Martin, Crescent B.; Stierman, Bryan; Yanovski, Jack A.; Hales, Craig M.; Sarafrazi, Neda; Ogden, Cynthia L.
Summary: Background: The association between body mass index (BMI) and adiposity differs by race/ethnicity. Objective: To examine differences in adiposity by race/Hispanic origin among US youth and explore how those differences relate to differences in BMI using the most recent national data, including non‐Hispanic Asian youth. Methods: Weight, height and DXA‐derived fat mass index (FMI) and percentage body fat (%BF) from 6923 youth 8–19 years in the National Health and Nutrition Examination Survey (NHANES) 2011–2018 were examined. Age‐adjusted mean BMI, FMI and %BF were reported. Sex‐specific linear regression models predicting %BF and FMI were adjusted for age, BMI category and BMI category*race/Hispanic origin interaction. Results: %BF was highest among Hispanic males (28.2%) and females (35.7%). %BF was lower among non‐Hispanic Black (23.9%) compared with non‐Hispanic White (26.0%) and non‐Hispanic Asian (26.6%) males. There was no difference between non‐Hispanic Black females (32.7%) and non‐Hispanic White (33.2%) or non‐Hispanic Asian (32.7%) females. FMI was higher among Hispanic youth compared with non‐Hispanic White youth. Among youth with underweight/healthy weight, predicted %BF and FMI were lower among non‐Hispanic Black males (−2.8%; −0.5) and females (−2.0%; −0.3), compared with non‐Hispanic White youth, and higher among Hispanic males (0.9%; 0.2) and females (2.0%; 0.5), while %BF but not FMI was higher among non‐Hispanic Asian males (1.3%) and females (1.4%). Among females with obesity, non‐Hispanic Asian females had lower %BF (−2.3%) and FMI (−1.7) than non‐Hispanic White females. Conclusions: Differences in %BF and FMI by race/Hispanic origin were not consistent by BMI category among US youth in 2011–2018.